A study on screening of high risk children for tuberculosis infection - V. K., Kishore V. R.; M., Hemasundar Rao (International Journal of Contemporary Pediatrics, 2019)
Background: Tuberculosis (TB) continues to be one of the most devastating and widespread infections in the world. Of the 9 million annual tuberculosis cases, about 1 million (11%) occur in children (under 15 years of age). Childhood tuberculosis is a neglected aspect of the tuberculosis epidemic. The objective of the study was to screen the children who are household contacts of TB, HIV and TB -HIV patients and identify the children with the type of tuberculosis (Latent and symptomatic) and treat accordingly there by reducing the transmission of disease, as these children may become open cases in the future. Methods: All the registered cases of active TB, TB-HIV and HIV were traced out from district unit of RNTCP, PHC, CHC in and around Nellimarla town (10 kms radius). These patients were interviewed for medical history, treatment history, duration of treatment and degree and duration of house hold contacts (primarily children between 1 to 14 years. Results: Out of 160 registered patients 91 patients were diagnosed as having symptomatic TB infection and 69 were diagnosed having latent TB infection, with most of the affected children being in the age group of 1 to 5 years). Majority of the symptomatic patients (46.15%) were household contacts of TB- HIV patients and majority of children (40.57%) with latent TB Infection are direct household contacts of open cases of TB alone. Of the symptomatic TB infection 74.72% had pulmonary TB and 25.28% had extra pulmonary TB. Conclusions: Tubercular lymphadenopathy is the most common manifestation of extra pulmonary TB followed by tubercular meningitis and among the tubercular lymphadenopathy the cervical lymphnodes are most commonly involved.